Becoming America An Exploration of American Literature from Precolonial to Post-Revolution - Kurant, Wendy (Open textbook library., 2018)
The University of North Georgia Press and Affordable Learning Georgia bring you Becoming America: An Exploration of American Literature from Precolonial to Post-Revolution. Featuring sixty-nine authors and full texts of their works, the selections in this open anthology represent the diverse voices in early American literature. This completely-open anthology will connect students to the conversation of literature that is embedded in American history and has helped shaped its culture. Features: Contextualizing introductions from Pre- and Early Colonial Literature to Early American Romanticism Over 70 historical images In-depth biographies of each author Instructional Design, including Reading and Review Questions This textbook is an open Educational Resource. It can be reused, remixed, and reedited freely without seeking permission.